PERHITUNGAN KORONA, AUDIBLE NOISE DAN RADIO INTERFERENCE PADA SALURAN UDARA TEGANGAN EKSTRA TINGGI 500 KV DENGAN VARIASI JARAK ANTAR KAWAT DAN JARAK ANTAR SIRKIT - Saraswati, Amalia; Sukmadi, Tejo; Handoko, Susatyo (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
Abstract Electric power delivering from power plant to load needs power transmission system with low energy loss and low voltage regulation. Extra high voltage can reduce the energy loss but it results corona. Corona produces corona loss and gives negative impact to the environment such as audible noise (AN) and radio interference (RI). Space conductor is one factor that affects the corona loss. In this final project will calculate corona loss, audible noise and radio interference under extra high voltage overhead lines 500 kV. The calculation will be held in the variation of cross arm and the variation of space conductor. Then, corona loss, AN and RI value will be compare to the permission value. Analysis result shows that corona loss value in single line configuration is smaller than corona loss value in double line configuration. Conductor space change has dominant influence to modify corona loss value, AN and RI value. It is more dominant than cross arm space change. Calculation with the configuration that suitable with SNI 04-6918-2002 shows that AN and RI value is lower than Perry Criteria and SPLN 46-1-1981 about AN maximum limitation guide and IEEE Radio Noise Design Guide about RI maximum limitation. Keyword : conductor space, cross arm space, corona, audible noise, radio interference